Combined immunodeficiency caused by a loss-of-function mutation in DNA polymerase delta 1 - Cui, Ye; Keles, Sevgi; Charbonnier, Louis-Marie; Julé, Amélie M.; Henderson, Lauren; Celik, Seyma Celikbilek; Reisli, Ismail; Shen, Chen; Xie, Wen Jun; Schmitz-Abe, Klaus; Wu, Hao; Chatila, Talal A. (Journal of allergy and clinical immunology, 2020)
Mutations affecting DNA polymerases have been implicated in genomic instability and cancer development, but the mechanisms by which they can affect the immune system remain largely unexplored. We sought to establish the role of DNA polymerase δ1 catalytic subunit (POLD1) as the cause of a primary immunodeficiency in an extended kindred. We performed whole-exome and targeted gene sequencing, lymphocyte characterization, molecular and functional analyses of the DNA polymerase δ (Polδ) complex, and T- and B-cell antigen receptor repertoire analysis. We identified a missense mutation (c. 3178C>T; p.R1060C) in POLD1 in 3 related subjects who presented with recurrent, especially herpetic, infections and T-cell lymphopenia with impaired T-cell but not B-cell proliferation. The mutation destabilizes the Polδ complex, leading to ineffective recruitment of replication factor C to initiate DNA replication. Molecular dynamics simulation revealed that the R1060C mutation disrupts the intramolecular interaction between the POLD1 CysB motif and the catalytic domain and also between POLD1 and the Polδ subunit POLD2. The patients exhibited decreased numbers of naive CD4 and especially CD8 T cells in favor of effector memory subpopulations. This skewing was associated with oligoclonality and restricted T-cell receptor β-chain V-J pairing in CD8+ but not CD4+ T cells, suggesting that POLD1R1060C differentially affects peripheral CD8+ T-cell expansion and possibly thymic selection. These results identify gene defects in POLD1 as a novel cause of T-cell immunodeficiency. [Display omitted]